Extraction, purification and antioxidant activity of flavonoids from Potentilla anserina L - Gao, Dandan; Yang, Xuankang; Lu, Danqi; Wang, Chenchen; Wang, Jiwen; Li, Huaxin; Guo, Xingchen (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPotentilla anserina L., a traditional Chinese medicinal herb, is valued for its edible, medicinal, and ornamental properties.MethodsIn this study, flavonoids were extracted from Potentilla anserina L. using ultrasonic-assisted extraction. The extraction process was optimized through response surface methodology, followed by separation and purification using Sephadex G-100 gel chromatography. Finally, the antioxidant activity of the extracted flavonoids was evaluated.ResultsThe results showed that the optimal extraction conditions were 60% ethanol concentration, an ultrasonic temperature of 50°C, ultrasonic power of 400 W, and ultrasonic time of 180 min. Under these conditions, the average extraction yield of flavonoids from Potentilla anserina L. was 3.74 ± 0.06 mg/g. The crude flavonoid extract was purified by Sephadex G-100 gel chromatography, yielding two fractions, LF-1 and LF-2, which accounted for 63.34% and 25.79% of the crude extract, respectively.DiscussionThe results of in vitro antioxidant activity experiments demonstrated that both fractions (LF-1 and LF-2) exhibited significant antioxidant activity, showing a dose-dependent capacity. These findings provide a theoretical basis for the further development and utilization of flavonoids from Potentilla anserina L..